Pengaruh Kecerdasan Spiritual, Kecerdasan Emosional dan Motivasi Terhadap Kinerja Pegawai Pada PT. Anugerah Putra Property - Ulul Absorul Hidayah; N. Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract This research uses descriptive research method. The method of data analysis in this study uses descriptive analysis, which is an analysis used to describe the characteristics of the study, the respondents studied and the data collected. After that the discussion is done descriptively. In this study the independent variables consisted of Emotional Intelligence (X1) Spiritual Intelligence (X2), and Motivation (X3) while the dependent variable was Employee Performance (Y). To determine whether there is an influence of the independent variable there is a dependent variable, then testing the hypothesis proposed in this study. The testing method for the proposed hypothesis is tested simultaneously using the T test, F test, and testing the coefficient of determination (R2). The results of this study indicate emotional intelligence, spiritual intelligence and motivation have a significant influence on the performance of employees of PT. Anugerah Putra Properti. Keyword : Intelligence, emotional, spiritual, performance